2019
DOI: 10.1186/s13068-019-1452-5
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal domain replacement changes an archaeal monoacylglycerol lipase into a triacylglycerol lipase

Abstract: Background Lipolytic enzymes of hyperthermophilic archaea generally prefer small carbon chain fatty acid esters (C 2 –C 12 ) and are categorized as esterases. However, a few have shown activity with long-chain fatty acid esters, but none of them have been classified as a true lipase except a lipolytic enzyme AFL from Archaeglobus fulgidus . Thus, our main objective is to engineer an archaeal esterase into a true therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The new thermoalkaliphilic lipolytic enzyme can be designed in the following ways: (i) inserting the C‐terminal extended region of MAS1 into LipA at the same place and substituting the residue Gly153/Cys153 for proper disulfide bond formation, (ii) inserting N‐terminal extended region of MAS1 into LipA at the same place and substituting the residue Ser32/Cys32 for proper disulfide bond formation, and (iii) creating the metal ion center at the C terminus mimics to MAS1 by substituting the residue. In recent years, many studies have been reported on lipolytic enzymes using the MD approach to alter the enzyme properties 13,47 . Singh et al explored the thermostability properties of Bacillus subtilis lipase using the MD simulation approach 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new thermoalkaliphilic lipolytic enzyme can be designed in the following ways: (i) inserting the C‐terminal extended region of MAS1 into LipA at the same place and substituting the residue Gly153/Cys153 for proper disulfide bond formation, (ii) inserting N‐terminal extended region of MAS1 into LipA at the same place and substituting the residue Ser32/Cys32 for proper disulfide bond formation, and (iii) creating the metal ion center at the C terminus mimics to MAS1 by substituting the residue. In recent years, many studies have been reported on lipolytic enzymes using the MD approach to alter the enzyme properties 13,47 . Singh et al explored the thermostability properties of Bacillus subtilis lipase using the MD simulation approach 48 .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many studies have been reported on lipolytic enzymes using the MD approach to alter the enzyme properties. 13,47 Singh et al explored the thermostability properties of Bacillus subtilis lipase using the MD simulation approach. 48 Recently, Dong et al improved the thermostability of LipA.…”
Section: F I G U R Ementioning
confidence: 99%
“…Swapping lids with non‐lipase lids such as esterases and carbohydrases may have great advantages in designing a hyperfunction lipase for industrial applications. For example, the monoacylglycerol lipase from Thermococcus onnurineus was constructed into a triacylglycerol lipase by replacing lid swapping with the lid domain of TLL (Soni et al., 2019). In addition, the constructed lipase was shown with high activity toward castor oil and has a potential application in castor oil biorefinery to obtain value‐added chemicals.…”
Section: Strategies Of Rebuilding the Lipase Lid For Food Applicationsmentioning
confidence: 99%
“…For most lipases, entry to the active site comprising of a catalytic triad is protected by a lid structure that consists of α‐helices, joined by a loop to the body of a lipase. Many lipase variants have been generated by methods (Table I), like insertion of a disulfide bridge in the hinge region of the lid, lid swapping [14], and so on, altering its substrate specificity, activity profile, and thermostability (Fig. 2).…”
Section: Discovery Of Lipolytic Enzymes and Protein Engineeringmentioning
confidence: 99%